2010
DOI: 10.3389/fnene.2010.00012
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution optical functional mapping of the human somatosensory cortex

Abstract: Non-invasive optical imaging of brain function has been promoted in a number of fields in which functional magnetic resonance imaging (fMRI) is limited due to constraints induced by the scanning environment. Beyond physiological and psychological research, bedside monitoring and neurorehabilitation may be relevant clinical applications that are yet little explored. A major obstacle to advocate the tool in clinical research is insufficient spatial resolution. Based on a multi-distance high-density optical imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
71
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 45 publications
(71 reference statements)
4
71
1
1
Order By: Relevance
“…Previous comparisons between fMRI and DOT have examined the co-localization between the two modalities in visual (Zhang et al, 2005) and motor Koch et al, 2010) cortices. However, these studies did not perform quantitative voxel-by-voxel comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous comparisons between fMRI and DOT have examined the co-localization between the two modalities in visual (Zhang et al, 2005) and motor Koch et al, 2010) cortices. However, these studies did not perform quantitative voxel-by-voxel comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not perform quantitative voxel-by-voxel comparisons. The motor papers used qualitative means to infer image agreement by projecting the fMRI data to individual DOI measurements at the scalp surface , or used a generic head model for the forward light modeling rather than using the subject-specific anatomy to generate a realistic photonpropagation model (Koch et al, 2010) and then projected the data from the 'model head' onto the subject specific MRI anatomy. In contrast this visual study compared fMRI activations to DOT reconstructions in a subject-specific brain volume.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We deem depth resolution necessary to clearly increase sensitivity to the bolus passage in cerebral tissue. This may be afforded by multi-distance approaches (as is currently being tested by our group along the principles of [93]), by frequency-domain [94] and ideally by time-resolved approaches [66]. Options to use ICG fluorescence to enhance sensitivity or assess dye extravasation await further evaluation in a clinical setting [95].…”
Section: (D) Perfusion Assessment By a Dye-bolus Techniquementioning
confidence: 99%
“…While most hemodynamic-based neuroimaging research studies in adult subjects are typically performed using functional magnetic resonance imaging (fMRI), its relative high cost, fixed scanner locations and physical constraints during imaging, limit fMRI's translation as a bedside clinical tool [10]. DOT has shown a strong potential in clinical application specifically for neonate and long-term bedridden patients [11] and NIR studies of the human brain have demonstrated its ability to recover abnormalities as haemorrhage detection from stroke patients [12] with accurate recovery of stimulated activations [13][14][15] and functional networks [5,16,17].…”
Section: Introductionmentioning
confidence: 99%